The implementation of teaching Science and Mathematics in English at secondary school in Kelantan / Iszam Hayati Hamat...[et al.] - Hamat, Iszam Hayati; Borhanudin, Bazila; Soberi, Nurul Falihin; Mohd Fauzi, Mohamad Luthefi; Mohd Hanif, Mohd Afiq (2010)
Teaching of Science and Mathematics in English TeSME, more frequently referred to as PPSMI(Pengajaran dan Pembelajaran Sains dan Matematik dalam Bahasa Inggeris) is a policy involving the change of medium of instruction for these two subjects from Malay which is the National Language of Malaysia to English. The implementation of PPSMI seems to have resulted in several issues and problems that have required attention. This article reports on part of an on-going study that focuses on the demographic profiles and perceptions of learners with limited English proficiency. The purpose of the study was to find out the relationship between student’s attitude and their achievement towards learning English in mathematics and science. In implementing English language as a second language in school, normally teachers who are teach in school at rural area usually faced more problems compare to the teachers who are teach English in urban school. One of the objectives of this study to know how far that statement can be accepted and the research will handle about the problems of teaching English as a secondary language, whether the students agree or disagree about this. The result showed that the highest percentage of students disagree for the implementation of study mathematics and science in English. It can be prove by the questionnaire and question test that will be given for them.